Estimation of Fatigue Deformation for Polyetheretherketone (PEEK) and Cast Cobalt-Chromium Circumferential Clasps: A comparative study - Hussein T. Abed; Aliaa W. Al-Omari (University of Mosul, College of Dentistry, 2022)
Aims: This in-vitro study aimed to compare the fatigue deformation of Polyetheretherketone (PEEK) and Cobalt-Chromium (Co-Cr) clasps by mechanical cycling test simulating ten years of use. Materials and Methods: 72 clasps samples were fabricated on a standardized e-max upper right first premolar; it is divided into 24 Co-Cr clasps, and 48 PEEK clasps which were subdivided into two halves (2.4, and 3.00) mm width respectively. Each group was further subdivided (n=8 clasps) according to the amounts of abutment undercut (0.25, 0.50, and 0.75) mm respectively. Each clasp was digitally pictured by a microscope before cycling, and then mechanically cycled by a specifically designed insertion-removal apparatus for 15000 times on its specific abutment crown, and at the end of 15000 cycles, each clasp was digitally re-pictured, and the distance between the clasp tips in millimeter of the pre and post cycling pictures were measured with specific analyzing computer program. Results: The fatigue deformation of Co-Cr clasps was higher significantly than the PEEK clasps for the three undercuts. Deeper undercuts showed a significantly higher fatigue deformation for Co-Cr clasps but not significant for PEEK clasps. Conclusion: The fatigue deformation of PEEK clasps with both widths after 15000 cycles of insertion/removal was lower than Co-Cr clasps fatigue deformation.